ผลของสมบัติของไหลที่มีต่อพฤติกรรมของลำพุ่งความเร็วสูง Effect of Liquid Properties on High Speed Liquid Jets Behavior - สิทธิวงษ์, วุฒิชัย; สีหานาม, วิระพันธ์; เพียรทอง, กุลเชษฐ์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมของลำพุ่งความเร็วสูงและคลื่นกระแทก (Shock Wave) ของเหลวที่มีสมบัติต่างกัน ประกอบด้วย นํ้า (Water) นํ้ามันดีเซล (Diesel Fuel) และนํ้ามันสบู่ดำ (Jatropha Curcas Oil) ที่กำเนิดจากหัวฉีดเครื่องยนต์ดีเซลแบบเดือย (Pintle Nozzle) ขนาดรูฉีด (Orifice) 0.8 mm ด้วยวิธี Projectile Impact Driven (PID) ผลการทดลองบันทึกด้วยกล้องถ่ายภาพ วิดีโอความเร็วสูง (High Speed Video Camera) ร่วมกับเทคนิคชาร์โดว์กราฟ จากการทดลองพบว่า ความเร็วเริ่มต้นของนํ้ามันดีเซลมีค่าสูงสุดประมาณ 850 m/s และนํ้ามันสบู่ดำมีความเร็วเริ่มต้นประมาณ 250 m/s นอกจากนี้จากภาพถ่ายเห็นพฤติกรรมของลำพุ่งของเหลวและคลื่นกระแทกชัดเจน รูปทรงของ ลำพุ่งนํ้าแตกต่างจากลำพุ่งของนํ้ามันดีเซลและนํ้ามันสบู่ดำ กรณีคลื่นกระแทกของนํ้ามันสบู่ดำจะแตกต่าง จากกรณีอื่นคือการเกิดคลื่นกระแทกเป็นแบบ Multiple Shock Wave Abstract The aims of this research are to study high velocity liquid jets and shock wave behavior of liquids with different properties. The liquid examined in this research consisted of water, diesel fuel and jatropha curcas oil, and High velocity liquids jets were generated using the projectile impact driven (PID) method along with a pintle diesel engine nozzle with a 0.8 mm orifice diameter. The experiment results were recorded by using a high speed video camera and shadowgraph technique. From experimental results, it is found that the diesel fuel liquid jets have the highest initial velocity of about 850 m/s while the jatropha curcas oil has the lowest initial velocity of about 250 m/s. According to recorded data, high velocity water jets differs in shape and behavior from diesel fuel and jatropha curcas oil jets. This and other liquid jet and shock wave behavior are clearly illustrated in recorded data. As a result, multiple shock waves are generated from jatropha curcas oil with high velocity liquid jets. This is in sharp contrast to the liquid jets creating with diesels fuel and water.